The effect of work discipline and work motivation toward civil servants’ performance in kerenci regency population and civil registration office - Riswanto Riswanto; Dasman Lanin; Syamsir Syamsir (Fakultas Ilmu Pendidikan UNP)
This study aims to reveal the effect of work discipline and motivation on civil servants performance working at Kerinci Regency Population and Civil Registration Office, because there is a problem the employee performance it is proven by preliminary data that researchers get there are still targets that have not been fully realized. This research used quantitative method. The population of this study was all civil servants serving in the Kerinci Regency Regional Secretariat. Respondents in this study were amounted to 96 samples. The data collection technique used in this study was proportional stratified random sampling technique. The data was collected through questionnaires that have been tested of their validity and reliability in advance, both the content and empirical test items in the field. The data analysis technique used in this research was multiple regressions. The results showed that there is a significant effect of work discipline and motivation on civil servants performance working at Kerinci Regency Population and Civil Registration Office. This means that higher-level work discipline and motivation will improve civil servants performance.